Using Canva in Creating and Designing E-Module for English Language Teaching - Tira Nur Fitria (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2024)
The utilization of learning material via the use of technology is interesting. Visual, audio, and audiovisual learning mediums are all options. Memorable and simple-to-understand learning activities may be created using appealing learning material. This study simulates Canva in making and designing an e-module in English material. This research is descriptive qualitative. The analysis shows that Canva is an online graphic design tool that allows educators to generate a variety of creative products such as e-modules of teaching materials. This app can be used to design learning media with attractive templates, and a varied presentation of shapes, images, colors, and letters. To use the Canva app, we create a Canva account on canva.com, choose a template for design, design (insert elements), choose a background, edit the background, add texts, upload images/audio/videos, insert links, download or share designs e-module. Canva is a site that offers both free and paid (freemium) access to a wide variety of design tools and options. Canva has provided 'graphics capabilities for users who 'cannot or are not good at designing' by providing various templates ranging from lawyers, elements (icons, photos, lines, illustrations), text with various fonts, and 4) backgrounds. So, the 'material' has been presented and the users just have to create it. Teachers/lecturers may find Canva to design learning media and develop instructional material. By using Canva, teachers/lecturers can teach material, knowledge, creativity, and skills that will be obtained for students, so that this media can also be used in various areas of their lives.